2018
DOI: 10.1161/jaha.118.009175
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Noninvasive Assessment of Lung Fluid Volume and Invasively Measured Cardiac Hemodynamics

Abstract: Background Right heart catheterization is the gold standard in clinical practice for the assessment of cardiovascular hemodynamics, but it is an invasive procedure requiring expertise in both insertion and reading. Remote dielectric sensing (Re DS ) is a noninvasive electromagnetic‐based technology intended to quantify lung fluid content. Methods and Results In this prospective single‐center study, Re DS readings wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 33 publications
2
41
1
3
Order By: Relevance
“…We recently showed that the ReDS measurement correlated with the actual PCWP measured by RHC ( Fig. 2B ) ( 11 ). Given the high sensitivity and moderate specificity, we suggest using ReDS technology to screen for pulmonary congestion in the ambulatory setting.…”
Section: Introductionsupporting
confidence: 52%
“…We recently showed that the ReDS measurement correlated with the actual PCWP measured by RHC ( Fig. 2B ) ( 11 ). Given the high sensitivity and moderate specificity, we suggest using ReDS technology to screen for pulmonary congestion in the ambulatory setting.…”
Section: Introductionsupporting
confidence: 52%
“…Normal lung measures 20–35% lung fluid content (default target range). The measurement can be done without any skin contact in up to 45 s. Uriel et al 53 . showed using ReDS™ strong correlations in both tissue‐measured fluid content and haemodynamic measurements with pulmonary artery wedge pressure.…”
Section: Novel and Upcoming Devices And Technologiesmentioning
confidence: 99%
“…Radar-based sensors (utilizing low-power radio frequency wavelength) are embedded in a system which is used for heart failure management by measuring lung fluid content (ReDS Heart Failure monitor™, Sensible Medical, Netanya, Israel). [25][26][27] The system measures the dielectric properties of tissues. Low-power electromagnetic signals are emitted through the right mid-thorax, and the signals received after passing through the tissue reflect their combined dielectric properties.…”
Section: Vital Signs and Covid-19-focused Sensorsmentioning
confidence: 99%